Proceedings of the Forty-Eighth Annual ACM Symposium on Theory of Computing 2016
DOI: 10.1145/2897518.2897642
|View full text |Cite
|
Sign up to set email alerts
|

Parallel algorithms for select and partition with noisy comparisons

Abstract: We consider the problem of finding the k th highest element in a totally ordered set of n elements (Select), and partitioning a totally ordered set into the top k and bottom n − k elements (Partition) using pairwise comparisons. Motivated by settings like peer grading or crowdsourcing, where multiple rounds of interaction are costly and queried comparisons may be inconsistent with the ground truth, we evaluate algorithms based both on their total runtime and the number of interactive rounds in three comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…Adaptivity. The concept of adaptivity is generally well-studied in computer science, largely due to the role it plays in parallel computing, such as in sorting and selection [Val75, Col88,BMW16], communication complexity [PS84, DGS84, NW91], multi-armed bandits [AAAK17], sparse recovery [HNC09, IPW11, HBCN09], and property testing [CG17, BGSMdW12, CST + 17]. Beyond being a fundamental concept, adaptivity is important for applications where sequentiality is the main runtime bottleneck.…”
Section: Related Workmentioning
confidence: 99%
“…Adaptivity. The concept of adaptivity is generally well-studied in computer science, largely due to the role it plays in parallel computing, such as in sorting and selection [Val75, Col88,BMW16], communication complexity [PS84, DGS84, NW91], multi-armed bandits [AAAK17], sparse recovery [HNC09, IPW11, HBCN09], and property testing [CG17, BGSMdW12, CST + 17]. Beyond being a fundamental concept, adaptivity is important for applications where sequentiality is the main runtime bottleneck.…”
Section: Related Workmentioning
confidence: 99%
“…Similar bounds hold for rank-k in the comparison model (Theorem 2.16). This generalizes the 4-round O(n log n) algorithm of Braverman, Mao, and Weinberg [BMW16]. On the other hand, the query complexity is O(n + k log n) in the value model (Theorem 4.1).…”
Section: Introductionmentioning
confidence: 54%
“…Recently, Braverman, Mao, and Weinberg [BMW16] showed that for n strictly ordered (krank) elements the required query complexity is Ω(n log n) queries to find the maximum w.p. at least 1 − 1/poly(n).…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dwork et al [11] and Ailon et al [2] considered a related Kemeny optimization problem, where the goal is to determine the total ordering that minimizes the sum of the distances to different permutations. For top-k identification, Braverman et al [4] initiated the study of how round complexity of active algorithms can affect the sample complexity. Szörényi et al [27] studied the case of k = 1 under the BTL model.…”
Section: Related Workmentioning
confidence: 99%